Recent Progress on Protein-Polyphenol Complexes: Effect on Stability and Nutrients Delivery of Oil-in-Water Emulsion System - Li, Minghui; Ritzoulis, Christos; Du, Qiwei; Liu, Yefeng; Ding, Yuting; Liu, Weilin; Liu, Jianhua (Frontiers in Nutrition, 2021)
Oil-in-water emulsions are widely encountered in the food and health product industries. However, the unsaturated fatty acids in emulsions are easily affected by light, oxygen and heat, which leads to oxidation, bringing forward difficulties in controlling emulsion quality during transporting, storaging, and selling. Proteins are commonly used as emulsifiers that can enhance the shelf, thermal and oxidation stability of emulsions. Polyphenols are commonly found in plants and parts of the family have been reported to possess antioxidant, anticancer and antimicrobial activities. Numerous studies have shown that binding of polyphenols to proteins can change the structure and function of the latter. In this paper, the formation of protein–polyphenol complexes (PPCs) is reviewed with respect to their use as emulsifiers, using as starting point the (covalent or non-covalent) interactions between the two. In addition, the effects polyphenol binding on the structure and function of proteins are discussed. The effects of proteins from different sources interacting with polyphenols on the emulsification, antioxidation, nutrient delivery and digestibility of oil-in-water emulsion are also summarized. In conclusion, the interaction between proteins and polyphenols in emulsions is complicated and still understudied, thereby requiring further investigation. The present review results in a critical appraisal of the relevant state-of-the-art with a focus on complexes’ application potential in the food industry, including digestion and bioavailability studies.